Use of Number Card Playing Method to Improve Early Childhood Numeracy Skills - Damayanti Purnamasari Suci; Yunita Yunita; Miftahulkhair Miftahulkhair; Febriana Ekananda Suras (Universitas Negeri Makassar, 2022)
The improvement of numeracy skills carried out in group B through number card playing activities at PGRI Ujung Indah Kindergarten, Mallusetasi District, is expected to increase through this study. The approach used in this research is qualitative. This research uses classroom action research (Classroom Action Research). Data collection is carried out using observation and documentation methods, data is collected and then analyzed using descriptive analysis techniques through the initial elaboration of the research until the end of the treatment given. The study's results during the first treatment process showed a percentage rate of 20%. In cycle II there was an increase with a percentage of 87%. For the activity aspect of pairing numbers on objects from the lowest to the highest numbers, the number in cycle I was as much as 33%, and an increase in cycle II showed a rise to 87%. Based on this data, the indicator of learning success is achieved because it has been at ≥ 70%.